In Good Faith - Gilbert, Claire M.
1 online resource (353 pages)
Keywords: Claire M. Gilbert develops the notion of “fiduciary translation“ and uses it to illuminate the ways in which Arabic-Spanish translators in early modern Spain made themselves indispensable for the administration of the empire, despite the increased animosity Arabic speakers faced in the age of the Inquisition.